Gastrointestinal stability, physicochemical characterization and oral bioavailability of chitosan or its derivative-modified solid lipid nanoparticles loading docetaxel. (4th May 2017) - Shi, Li-Li; Lu, Jia; Cao, Yue; Liu, Jiang-Yan; Zhang, Xiao-Xue; Zhang, Hongjian; Cui, Jing-Hao; Cao, Qing-Ri
Abstract: Objective: The purpose of this study was to prepare the positively charged chitosan (CS)- or hydroxypropyl trimethyl ammonium chloride chitosan (HACC)-modified solid lipid nanoparticles (SLNs) loading docetaxel (DTX), and to evaluate their properties in vitro and in vivo . Methods: The DTX-loaded SLNs (DTX-SLNs) were prepared through an emulsion solvent evaporation method and further modified with CS or HACC (CS-DTX-SLNs or HACC-DTX-SLNs) via noncovalent interactions. The gastrointestinal (GI) stability, dissolution rate, physicochemical properties and cytotoxicities of SLNs were investigated. In addition, the GI mucosa irritation and oral bioavailability of SLNs were also evaluated in rats. Results: The HACC-DTX-SLNs were highly stable in simulated gastric and intestinal fluids (SGF and SIF). By contrast, the CS-DTX-SLNs were less stable in SIF than in SGF. The drug dissolution remarkably increased when DTX was incorporated into the SLNs, which may be attributed to the change in the crystallinity of DTX and some molecular interactions that occurred between DTX and the carriers. The SLNs showed low toxicity in Caco-2 cells and no GI mucosa irritations were observed in rats. A 2.45-fold increase in the area under the curve of DTX was found in the HACC-DTX-SLN group compared with the DTX group after the modified SLNs were orally administered to rats. However, the oral absorption of DTX-SLN or CS-DTX-SLN group showed no significant difference compared with that of DTX group. Conclusions: The positively charged HACC-DTX-SLNs with a stable particle size could provide the enhanced oral bioavailability of DTX in rats.